I/V characteristics of a ferroelectric nanofilm towards the hydrogen peroxide steam - Davtyan, A. A. (ՀՀ ԳԱԱ հրատ.)
The I/V characteristics of ferroelectric (barium-strontium titanate, BST) nano-film - based Pt-BST-Pt structure in the environment of the hydrogen peroxide (H2O2) steam in the temperature range of t=36...42օ C and densities of H2O2(0% (distilled water), 0,5%, 1%, 1,5% and 3%) is experimentally studied. It is justified that the BST membrane shows good sensitivity that can be used for the rapid and early invasive diagnosis of respiratory diseases. Sensitivity mechanisms are also proposed and discussed. Փորձնականորեն ուսումնասիրվել են ֆերոէլեկտրական նանոթաղանթի (բարիում- ստրոնցիում-տիտանատ՝ BST) վրա հիմնված Pt-BST-Pt կառուցվածքի I/V բնութագրերը t=36...42oC ջերմաստիճանային միջակայքում՝ տարբեր խտությամբ ջրածնի պերօքսիդի(0% (թորած ջուր), 0,5%, 1%, 1,5% եւ 3% H2O2) գոլորշիների առկայությամբ: Պարզվել է, որ BST թաղանթը դրսևորում է բարձր զգայնություն։ Նանոթաղանթի այդ հատկությունը կարող է օգտագործվել շնչառական հիվանդությունների արագ և վաղ ախտորոշման համար: Առաջարկվել և քննարկվել են նաև զգայնության մեխանիզմները: Экспериментально исследованы I/V характеристики ферроэлектрической (титанат бария-стронция, BST) нанопленки на основе структуры Pt-BST-Pt в среде паров пероксида водорода (H2O2) в интервале температур t=36...42oC и плотности H2O2 (0%(дистиллированная вода), 0,5%, 1%, 1,5% и 3%). Выявлено, что мембрана BST демонстрирует хорошую чувствительность. Это свойство может быть использовано для быстрой и ранней инвазивной диагностики респираторных заболеваний. Предложены и обсуждены механизмы чувствительности.
Keywords: Technology